2016
DOI: 10.1111/ejn.13414
|View full text |Cite
|
Sign up to set email alerts
|

Activation of cannabinoid receptor 2 attenuates mechanical allodynia and neuroinflammatory responses in a chronic post‐ischemic pain model of complex regional pain syndrome type I in rats

Abstract: Complex regional pain syndrome type 1 (CRPS-I) remains one of the most clinically challenging neuropathic pain syndromes and its mechanism has not been fully characterized. Cannabinoid receptor 2 (CB2) has emerged as a promising target for treating different neuropathic pain syndromes. In neuropathic pain models, activated microglia expressing CB2 receptors are seen in the spinal cord. Chemokine fractalkine receptor (CX3CR1) plays a substantial role in microglial activation and neuroinflammation. We hypothesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 77 publications
(110 reference statements)
3
23
0
Order By: Relevance
“…The dopaminergic neuron‐specific deletion of the CB 2 receptors allowed providing evidence of the contribution of both CB 1 receptors and CB 2 receptors in the cannabinoid tetrad task. This is consistent with preclinical studies showing that selective CB 2 receptor agonists exert an attenuation of neuropathic pain pathways in rodent pain models and suggest that CB 2 receptors may contribute to the physical effect resulting from ECS direct (or alcohol‐evoked) activation.…”
Section: Resultssupporting
confidence: 89%
“…The dopaminergic neuron‐specific deletion of the CB 2 receptors allowed providing evidence of the contribution of both CB 1 receptors and CB 2 receptors in the cannabinoid tetrad task. This is consistent with preclinical studies showing that selective CB 2 receptor agonists exert an attenuation of neuropathic pain pathways in rodent pain models and suggest that CB 2 receptors may contribute to the physical effect resulting from ECS direct (or alcohol‐evoked) activation.…”
Section: Resultssupporting
confidence: 89%
“…The increased CB2 receptor expression after peripheral nerve injury is highly restricted within the lumbar spinal cord microglia [ 6 ]. Moreover, the same pattern of CB2 receptor expression was observed in the model of spinal nerve transaction, osteoarthritis, and post-ischemic pain [ 7 9 ]. In addition, CB2 messenger RNA (mRNA) is also present in cultured spinal cord microglia cells [ 10 ].…”
Section: Introductionmentioning
confidence: 71%
“…This is consistent with elevation in CB2Rs and gene expression in DRG neurons and satellite glial cells in a rat neuropathic pain model 39 . Other preclinical studies using selective CB2R agonists have been shown to attenuate mechanical allodynia and neuroinflammatory responses in rodent pain models suggesting that CB2Rs are intricately involved in the attenuation of inflammatory and neuropathic pain pathways 39 42 . Ongoing studies of the CB2Rs and their possible roles in many pathological conditions including pain of different etiologies may be more complicated than previously appreciated.…”
Section: Discussionmentioning
confidence: 99%